Implementation Of Project-Basedd Learning In Improving Crtical Thinking Skills And Communication Skills Of Public Health Students - Adila Solida; Andy Amir (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
The project-based learning (PjBL) model is understood to improve student's abilities in the learning process. The use of conventional learning methods is still dominant in the Jambi University Public Health Department. Student-centered learning innovation is needed through the application of project-based learning models. The purpose of this study was to identify differences in critical thinking skills and student communication skills between the application of project-based learning and conventional learning in the National and Regional Health Development System courses. The research was conducted at the Jambi University Public Health Science Study Program for semester V students with a total of 36 students. The research design was a quasi-experiment involving an experimental class and a control class. The instruments used were test sheets with indicators of measuring critical thinking skills and oral communication skills test sheets and report assessment sheets. Data collection was done twice with pre-test and post-test. Data processing used statistical software. Data analysis was carried out in stages using the T-test. The results showed that there were differences in the critical thinking skills (p=0,002) and communication skills (p=0,004) of students between the application of project-based learning and the application of conventional learning. There is an effect of project-based learning on students' critical thinking skills and communication skills in the National and Regional Health Development System course.Project-based learning is recommended to be applied to every course in various study programs in higher education, especially case-based study materials. The PjBL method provides opportunities for students to be directly involved in completing projects to solve problems that are examined so that it is expected to be able to increase students' thinking power to think critically and hone communication skills by being actively involved in a complex learning process.